Treatment of patients with anorexia nervosa and comorbid post-traumatic stress disorder; where do we stand? A systematic scoping review - van den Berg, Elske; Pellemans, Kirsten; Planting, Caroline; Daansen, Peter; van Beers, Ella; de Jonge, Margo; Christ, Carolien; Dekker, Jack (Frontiers in Psychiatry, 2024)
Comorbid post-traumatic stress disorder in patients with anorexia nervosa may negatively affect the course of anorexia nervosa treatment, which is already challenging. There are currently no guidelines or recommendations on concurrent treatment approaches for both anorexia nervosa and post-traumatic stress disorder. This systematic scoping review aims to explore the feasibility, acceptability and effectiveness of psychological trauma-focused treatment concurrently offered to underweight patients receiving anorexia nervosa treatment.A multi-step literature search, according to an a priori protocol was performed. Databases PubMed, Embase, APA PsycINFO, Web of Science, Scopus and Cochrane Central were searched up to September 19 th 2022, and the search was rerun June 19 th 2023. For quality assessment, Risk of Bias in Non-randomised Studies-of Interventions tool was used.The extensive search yielded 1769 reports, out of which only three observational pilot studies, both English and German, published between 2004 and 2022, could be included.The included studies reported on a total of 13 female participants between 16 and 58 years old, with anorexia nervosa or otherwise specified feeding or eating disorder, baseline BMI ranging between 14.6 and 16.5, who received concurrent anorexia and post-traumatic stress disorder treatment. In all participants, the emotional and cognitive functioning was sufficient to process the offered trauma-focused interventions, despite their significantly low body weight.The findings of this review identify a dearth of treatment research on knowledge of concurrent trauma-focused treatments for patients with anorexia nervosa.Refraining patients with anorexia nervosa from trauma-focused treatment may not be warranted.